How to Negotiate Difficult Colonoscopy to Optimize Cecal Intubation Rate - Suharjo B Cahyono; Putut Bayupurnama (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2013)
Colonoscopy is the current standard method for evaluating colon. Cecal intubation rate is an important indicator of colonoscopy quality. In up to 10–20% colonoscopies, cecal intubation may be considered difficult.There are several consequences of low cecal intubation rate: it limits the efficacy of colonoscopy, increasing risk of complications and cost, and missing in detecting adenoma colorectal or other abnormal mucosa lesion.Failure to intubate the cecal can be a result of: (1) patients factors (female, older, diverticular disease, history of abdominal surgery, low body mass index, history of constipation, laxative use); (2) endoscopist factors (prior experience, the specific techniques and instrument used; (3) or some combination thereof. In an effort to solve these problems endoscopist should increase their technical manoeuvres (minimizing inflation and looping, using water–aided method, appropriate use of positional changes and abdominal pressure) and use various accessories methods (inserting a biopsy forceps through the biopsy channel, pediatric colonoscopy, variable stiffness colonoscopy).Keywords: cecal intubation rate, difficult colonoscopy, colonoscopy quality, water–aided colonoscopy